(untitled) (Annals of King Edward Medical University, 2020)
To assess the utility of Myelography in various spinal tumours, 42 patients were selected from the Neurosurgical unit of Lahore General Hospital and this study was carried out for one year from August 1993 to July 1994. All the patients underwent myelographic examination. Age range of the patients was between 22 and 67 years (mean 44.5 years). The commonest spinal tumour seen was Neurofibroma 21/42 (50.0). Others were meningioma 8/42 (19. 0%), metastases 6/42 (14.2%), lymphoma 3/42 (7.2%), ependymoma 2/42 (4.8%) and astrocytoma 2/42 (4.8%).The level at which these lesions were commonly seen was the thoracic spine 19/42 (45.2%) and the commonest nature of spinal lesion was intradural extramedullary tumour 23/42 (54.8%). Neurofibroma was mainly found to be intradural extramedullary in nature i. e., 17/21(80%). Meningioma’s accounted for 5/8 (62.5%) cases which were intradural extramedullary. All the cases of metastases 6/6 (100.0%) and lymphomas 3/3 (100.0%) were extradural. A lithe astrocytomas 2/2 (100.0%) were in trameduliary, whereas 1/2 (50.0%) of Ependymomas were intramedullary. The study concludes that myelography is specific in diagnosing the nature of the spinal tumours (i.e. extradural, intradural extramedullary or intramedullary) and localizing (he exact site and extent of the lesion, and assisting the neurosurgeon in excision and biopsy taking.